Wild fish are not a significant reservoir for Neoparamoeba pemaquidensis (Page, 1987) - Douglas-Helders, GM; Dawson, DR; Carson, J; Barbara Nowak (2002)
Amoebic gill disease (AGD), caused by the protozoan Neoparamoeba pemaquidensis (Page, 1987) is the most important disease affecting salmon farms in Tasmania. Reservoirs for this protozoan parasite are largely unknown. This study investigated wild fish as a potential reservoir of N. pemaquidensis. A total of 325 wild fish, comprising 12 different fish species, were caught from and around salmon farms and examined for the presence of AGD. None of the wild fish were infected with AGD. In a laboratory trial, seahorse, Hippocampus abdominalis, greenback flounder, Rhombosolea tapirina, and Atlantic salmon, Salmo salar, were challenged with N. pemaquidensis. Neoparamoeba pemaquidensis was detected on the gills on 10 of 15 (66.7%) flounder, nine of 24 (37.5%) seahorses, and six of six (100%) Atlantic salmon. However, paramoebae positive flounder and seahorse lacked the characteristic AGD gill pathology. It is concluded that AGD does not appear in wild fish and wild fish do not seem to be a reservoir of the pathogen.